Low Perinatal Androgens Predict Recalled Childhood Gender Nonconformity in Men. (March 2022) - Shirazi, Talia N.; Self, Heather; Rosenfield, Kevin A.; Dawood, Khytam; Welling, Lisa L. M.; Cárdenas, Rodrigo; Bailey, J. Michael; Balasubramanian, Ravikumar; Delaney, Angela; Breedlove, S. Marc; Puts, David A.
The contributions of gonadal hormones to the development of human behavioral sex differences are subjects of intense scientific and social interest. Isolated gonadotropin-releasing-hormone deficiency (IGD) is a rare endocrine disorder that can reveal a possible role of early gonadal hormones. IGD is characterized by low or absent gonadal hormone production after the first trimester of gestation, but external genitalia and hence gender of rearing are concordant with chromosomal and gonadal sex. We investigated recalled childhood gender nonconformity in men ( n = 65) and women ( n = 32) with IGD and typically developing men ( n = 463) and women ( n = 1, 207). Men with IGD showed elevated childhood gender nonconformity, particularly if they also reported undescended testes at birth, a marker of low perinatal androgens. Women with IGD did not differ from typically developing women. These results indicate that early androgen exposure after the first trimester contributes to male-typical gender-role behaviors in childhood.